1997
DOI: 10.1093/gerona/52a.3.m161
|View full text |Cite
|
Sign up to set email alerts
|

Self-Paced Resistance Training and Walking Exercise in Community-Dwelling Older Adults: Effects on Neuromotor Performance

Abstract: The two self-paced exercise protocols were effective at improving neuromotor performance and functional capacity in the study sample and show promise as a safe, effective, cost-efficient, acceptable exercise model for primary and secondary prevention in the general population of community-dwelling older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0
6

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 29 publications
7
79
0
6
Order By: Relevance
“…However, in this study, although leg muscle strength has improved, improvement of static balance was not seen. The reason seems to be that the subject's balanced capability baseline level was higher than in previous studies (Rikli and Edwards, 1991;Rooks et al, 1997;Englund et al, 2005). Differences in the age and previous activity levels of subjects may explain the difference of a subject's balanced capability baseline level.…”
Section: The Effect Of Exercise Intervention On Physical Performancementioning
confidence: 59%
See 2 more Smart Citations
“…However, in this study, although leg muscle strength has improved, improvement of static balance was not seen. The reason seems to be that the subject's balanced capability baseline level was higher than in previous studies (Rikli and Edwards, 1991;Rooks et al, 1997;Englund et al, 2005). Differences in the age and previous activity levels of subjects may explain the difference of a subject's balanced capability baseline level.…”
Section: The Effect Of Exercise Intervention On Physical Performancementioning
confidence: 59%
“…Additionally, Panton et al (1990) have also reported that there was no effect of training on the reaction time of elderly adults as a result of aerobic or resistance training over 26 weeks. However, Rooks et al (1997) have reported that not only resistance training but also walking for 10 months has improved simple reaction time (13%, 11%, respectively). Our study extends the previous findings of Rikli and Edwards (1991), showing that combined exercise intervention for elderly women can improve reaction time.…”
Section: The Effect Of Exercise Intervention On Physical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Some parents in consultation with the physiotherapist devised solutions such as using a vest to hold the weights. In the literature, other solutions for adding resistance to weightbearing exercise have included the use of a weighted skin-diving belt (Rooks et al 1997). Some participants had difficulties with their feet catching on the hollow aerobic step.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In addition, resistance training also prevents and rehabilitates orthopedic injuries, 1,2 and maintains functional stability and independence into older age. 3,4 The benefi ts of promoting resistance training in older people are especially important since the percentage of individuals 65 years and older in the U.S between 1995-2030 will increase by 107%, and those 85 and older will increase by 133%. Interestingly, those under the age of 65 will only increase by 21%.…”
Section: Introductionmentioning
confidence: 99%